Eleventh Five Year Plan 2007-2012 and Annual Plan 2007-2008 Draft Proposals Volume-II General Statement and Annexures - Planning Commission (Planning Commission, 2007)
Draft Eleventh Five Ayre Plan (2007-12) And Annual Plan - (2007-08) - Proposed Outlays Draft Eleventh Five Year Plan (2007-12) And Annual Plan - (2007-08) - Proposed Outlays (From State Budget) Draft Eleventh Five Year Plan (2007-12) And Annual Plan (2007-08) - Proposed Outlays (From Public Sector Enterprises) Draft Eleventh Five Year Plan (2007-12) And Annual Plan (2007-08) - Proposed Outlays (Rural Local Bodies)
Planning Department Government of Meghalaya